Debates in computing and ICT education - Younie, Sarah, 1967-; Bradshaw, Pete (Debates in subject teaching series, 2018)
Debates in ICT and Computing Education explores the major issues teachers encounter in their daily professional lives. It encourages critical reflection and aims to stimulate both novice and experienced teachers to think more deeply about their practice, and link research and evidence to what they have observed in schools. Chapters tackle established and contemporary issues enabling teachers to reach informed judgements and argue their point of view with deeper theoretical knowledge and understanding. Debates include teacherless classrooms; personalised learning; creativity; digital literacy; visual literacy; e-tools; learning platforms; and opportunities for lifelong learning.